(untitled) (Scientia Agricola, 2018)
This study evaluated pre-slaughter stress and its influence on the stress indicators, quality characteristics and sensory characteristics of Nile tilapia fillets. To this end, two experiments were conducted: (1) two transportation times (60 and 240 min), with a density of 200 kg m−3, were compared to control treatment fish (in which the fish were removed from the net cage and immediately euthanized); and (2) two transportation densities (100 and 400 kg m−3), transported for 180 min, compared with control treatment fish. In experiment 1, the transportation time of 60 min resulted in higher levels of serum cortisol and plasma glucose compared to the transportation time of 240 min and the control. Fish fillets transported for 240 min had higher water-holding capacity, less water loss by pressure and higher levels of juiciness compared to fish transported for 60 min. Color, pH and water loss during cooking were not affected by transportation time. In experiment 2, transportation densities of 100 and 400 kg m−3 did not significantly affect the stress indicators nor the instrumental quality parameters of the fillets, but fish transported at 400 kg m−3 showed better visual acceptance by panellists.